35 Electrophysiology and electrostimulation: experience. (8th December 2021) - Santucci, Stefano; Negossi, Davide; Emanuelli, David; Paoloni, Valentina; Biondi, Federico; Santucci, Matteo; Marzuolo, Cinzia
Abstract: In the last 50 years, cardiac electrophysiology has undergone rapid technological development which has led to a numerical increase in both patients who have been able to benefit from the therapies of rediscovery and rhythm control, and of the devices. The activity of an electrophysiology and electrostimulation room is based on the intensive use of ionizing radiation even if electrophysiology studies, ablation, and cryoablation techniques have benefited from the support of computerized electroanatomical mapping systems with consequent dose reduction. Over the years, the instruments to be managed inside the room have increased both in complexity and numerically. Starting from the biventricular PM, we go through the implantation of subcutaneous defibrillators up to the transseptal ablations. Patient management requires additional skills that each member of the team must possess. Continuous training and updates are of fundamental importance. The purpose of this work is our experience based on the activity now more 10 years.